Prevention of materno‐foetal transmission of hepatitis B in sub‐Saharan Africa: the evidence, current practice and future challenges. Issue 6 (June 2014) - Howell, J.; Lemoine, M.; Thursz, M.
Summary Hepatitis B (HBV) infection is highly endemic in sub‐Saharan Africa (SSA), where more than 8% of the population remain chronic HBV carriers. SSA has one of the highest HBV‐related liver cancer rates in the world (CA Cancer J Clin, 55, 2005, 74) and HBV‐related liver cancer is the most common cause of premature death in West Africa (Lancet Oncol, 9, 2008, 683; Hepatology, 39, 2004, 211). As such, HBV represents a significant global threat to health in the African continent. Most SSA countries have elected to vaccinate all children against HBV through the WHO‐sponsored Expanded Program of Immunization and the current recommendation from WHO‐AFRO is for birth‐dose HBV vaccination to prevent maternal/child transmission (MFT) and early horizontal transmission of HBV. However, in Africa, HBV vaccine coverage remains low and HBV birth‐dose vaccination has not been implemented. HBV transmission from mother to child in the early perinatal period therefore remains a significant contributor to the burden of HBV‐related disease in SSA. This review explores the evidence for materno‐foetal transmission of HBV in SSA, outlining current practice for HBV MFT prevention and identifying the significant challenges to implementation of HBV prevention in SSA.